The Political Economy of Taxation: Power, Structure, Redistribution - Stanley L. Winer (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this chapter I provide an overview of the political economy of taxation in democratic states by considering the three most important issues in the field: (1) the evolution of the power to tax in (what are now) the mature constitutional democracies; (2) the nature and determinants of modern tax structures; and (3) redistribution in pluralistic societies over various horizons and in the face of economic shocks. The discussion considers the ideas and models that have arisen as scholars have grappled with these related issues, and points to some of the outstanding problems that may be worth pursuing in future research.
Keywords: D72; D78; H20; H24; 330; taxation; Oxford Handbook; political economy; public choice; power to tax; tax structure; fiscal redistribution